2020
DOI: 10.3390/cells9122635
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Metabolism in Cancer

Abstract: The interest in fructose metabolism is based on the observation that an increased dietary fructose consumption leads to an increased risk of obesity and metabolic syndrome. In particular, obesity is a known risk factor to develop many types of cancer and there is clinical and experimental evidence that an increased fructose intake promotes cancer growth. The precise mechanism, however, in which fructose induces tumor growth is still not fully understood. In this article, we present an overview of the metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 100 publications
1
23
0
1
Order By: Relevance
“…We previously reported that cancer cells such as acute myeloid leukemia cells exhibited enhanced fructose utilization under low glucose conditions and that pharmacologic blockade of fructose utilization suppressed AML cell proliferation and enhanced the therapeutic efficacy of Ara-C 2 . Our recent findings, along with reports from other groups 14 , suggest that fructose is a preferred carbon source for many cancer cells. High expression of the fructose transporter SLC2A5/GLUT5 was found in multiple types of cancers, enabling increased uptake of fructose from the microenvironment and enhanced cancer growth and development.…”
supporting
confidence: 79%
“…We previously reported that cancer cells such as acute myeloid leukemia cells exhibited enhanced fructose utilization under low glucose conditions and that pharmacologic blockade of fructose utilization suppressed AML cell proliferation and enhanced the therapeutic efficacy of Ara-C 2 . Our recent findings, along with reports from other groups 14 , suggest that fructose is a preferred carbon source for many cancer cells. High expression of the fructose transporter SLC2A5/GLUT5 was found in multiple types of cancers, enabling increased uptake of fructose from the microenvironment and enhanced cancer growth and development.…”
supporting
confidence: 79%
“…This enzyme hydrogenates Fructose to Sorbitol in Fructose catabolism pathway. Subsequently, sorbitol is dehydrogenated to glucose via AKR1B1 enzyme providing fuel for cells ( 132 ). In addition, excess glucose promotes EMT through autocrine TGFβ stimulation ( 133 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these metabolic changes involve the increased consumption of fructose in low glucose conditions or the regulation of enzymes to support alternative metabolic pathways. There have been comprehensive studies and reviews documenting the role of fructose in cancer metabolism [ 59 , 60 , 61 , 62 ]; therefore, we will briefly focus on some recent findings related to fructose metabolism through central carbon pathways. Since the consumption of fructose has increased over the past decades, understanding how cancers metabolize fructose has become more critical and encourages a consideration of dietary changes or alternative therapeutic strategies that might target fructose-related pathways to mitigate cancer progression.…”
Section: Fructose Metabolism Disordersmentioning
confidence: 99%